2022
DOI: 10.12965/jer.2244122.061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bilateral isokinetic and isometric strength differences in elite young male and female taekwondo athletes

Abstract: Definition of strength imbalance between legs and muscles does not only play a decisive role for higher performance but also prevents sport injury. The purpose of this study was to determine bilateral differences on isokinetic and isometric strength of knee extensor and flexor muscles in male and female elite young taekwondo athletes. Ten male (age: 19.40± 0.84 years) and female (age: 18.24± 1.42 years) taekwondo athletes of the Turkish national team between 17–20-year of age participated in the study. Concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(57 reference statements)
2
4
0
Order By: Relevance
“…In addition, the statistical difference between H/Q ratios (p<0.05) shows that taekwondo athletes have lower H/Q strength ratios. In previous isokinetic studies, it was determined that the knee isokinetic strength of taekwondo (Choi et al, 2021;El-Ashker et al, 2022;Hammami et al, 2013;Harbili et al, 2022;Kang et al, 2021) and wrestling (Çimen Polat et al, 2018;Drid et al, 2009;Hoseini et al, 2022;Kraemer et al, 2001;Tatlici, 2021;Tatlici et al, 2021) athletes supported our research results. This result may be due to the fact that taekwondo explosively trains roundhouse and rotating kicks that require lower extremity FLX and EXT strength.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the statistical difference between H/Q ratios (p<0.05) shows that taekwondo athletes have lower H/Q strength ratios. In previous isokinetic studies, it was determined that the knee isokinetic strength of taekwondo (Choi et al, 2021;El-Ashker et al, 2022;Hammami et al, 2013;Harbili et al, 2022;Kang et al, 2021) and wrestling (Çimen Polat et al, 2018;Drid et al, 2009;Hoseini et al, 2022;Kraemer et al, 2001;Tatlici, 2021;Tatlici et al, 2021) athletes supported our research results. This result may be due to the fact that taekwondo explosively trains roundhouse and rotating kicks that require lower extremity FLX and EXT strength.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that knee FLX and EXT strength results measured with isokinetic dynamometers are highly reliable (Brown et al, 2005;Feiring et al, 1990;Hartmann et al, 2009;Jenkins et al, 2015;Maffiuletti et al, 2007;Sole et al, 2007). Therefore, in sports like taekwondo and wrestling where the legs are actively used, isokinetic dynamometers are widely preferred for measuring knee flexion and extension strength or quadriceps (Q) and hamstring (H) muscle strength (Coban et al, 2021;Hammami et al, 2013;Harbili et al, 2022;Kang et al, 2021;Tatlici et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The trunk was the least injured area, which may be related to the use of protective gear in these areas during training and competition [26,27] The injury of female athletes was higher than that of male athletes [1.2], which maybe because men had 20%-30% higher concentric and isometric knee extensor and flexor strength than females in both legs. [28] In the non-contact sport, Poomsea athletes' strain and joint dysfunction were the most common injury types, and lower limbs were the most common injury sites. In addition, lower limb injuries were more likely in women than in men, and the…”
Section: Case Of Injurymentioning
confidence: 99%
“…The athlete's leg was set to a zero-degree angle at full extension, and a 90-degree flexion angle was designated, resulting in a movement range spanning from 0 to 90 degrees. For the isometric measurements, the leg angle was 45 degrees, and the contraction duration was 5 s. Only EXT strength was measured in isometric contractions [43].…”
Section: Isokinetic Strength Evaluation Of Muscular Performancementioning
confidence: 99%